CURRENT SITUATION OF AGRICULTURAL EXTENSION IN ENTREPRENEURSHIP AND COOPERATIVES (Third Sector Social Economic Review, 2017)
Today entrepreneurship has different describings it can be also defined as making systematic, logical and feasible imaginative thinking. One of the most basic features of an entrepreneur is to be creative and to innovate or make a difference. So we can say entrepreneurship is therefore an innovation activity. The development of a new production method, the production of a new commodity, the discovery and restructuring of a new source of raw material, the creation of a new market, and so on. It is innovation. According to the results of rural surveys, social networking plays an important role in accepting and rejecting innovations in agricultural extension services.Agricultural extension is a bridge between science and field practices, another wordsIt is a science that applies the rural innovation to the farmers in a training process and communicates the problems identified in the rural areas to the relevant institutions and organizations. Thus agricultural extension allows the innovations to spread consciously in the countryside on the otherhand it contributes to the development of the technology produced in research institutions during this activity it leads to entrepreneurship.This paper will examine the current situation of cooperative agricultural publication service which is leading to entrepreneurship.
Keywords: Entrepreneurship; Cooperative; Agricultural Extension; Communication; Innovation